Gender Differences in Cognitive Styles Distinguishing Excellent, Normal and Late Achievers: A comparative study on a sample of secondary school girls - Nawafleh , Ahmad (Dirasat: Educational Sciences, 2020)
The purpose of this study was discovering gender differences in cognitive styles distinguishing excellent, avarage and late achievers. The study was conducted on (280) secondary school students. To achieve this purpose, two instruments were used infusive figures test (group picture) and familiar shapes intermarriage (FSI). The study revealed that among of the two cognitive styles impulsive and reflective, the impulsive cognitive style dominanted among secondary school male and female students and among the dependence and independence of perceptual, the independence of perceptual domainated. The study also revealed statistically significant differences for the two variables related to gender and average on the two fields of cognitive style where high achievers outperform average ones of both genders, as well as, statistically significant differences differences for two variables (gender, average on the field of cognitive style (dependence vs. independence) where high achievers outperform average ones from both genders